Oxford Shakespeare : Hamlet. - Shakespeare, William (Oxford University Press, 1987)
In his introduction Professor Hibbard explains the process by which variant texts were fused in the 18th century to create the most commonly used text of today. Drawing on critical and theatrical history, he shows how this fusion makes 'Hamlet' seem a much more 'problematic' play than it was when it originally appeared in 1623.